Post kala-azar dermal leishmaniasis in the Indian sub-continent: challenges and strategies for elimination - Kumar, Awnish; Singh, Vishal Kumar; Tiwari, Rahul; Madhukar, Prasoon; Rajneesh,; Kumar, Shashi; Gautam, Vibhav; Engwerda, Christian; Sundar, Shyam; Kumar, Rajiv (Frontiers in Immunology, 2023)
Visceral leishmaniasis (VL) is a severe and often fatal form of leishmaniasis caused by Leishmania donovani in the Indian sub-continent. Post Kala-azar Dermal Leishmaniasis (PKDL) is a late cutaneous manifestation of VL, typically occurring after apparent cure of VL, but sometimes even without a prior history of VL in India. PKDL serves as a significant yet neglected reservoir of infection and plays a crucial role in the transmission of the disease, posing a serious threat to the VL elimination program in the Indian sub-continent. Therefore, the eradication of PKDL should be a priority within the current VL elimination program aimed at achieving a goal of less than 1 case per 10,000 in the population at the district or sub-district levels of VL endemic areas. To accomplish this, a comprehensive understanding of the pathogenesis of PKDL is essential, as well as developing strategies for disease management.This review provides an overview of the current status of diagnosis and treatment options for PKDL, highlighting our current knowledge of the immune responses underlying disease development and progression. Additionally, the review discusses the impact of PKDL on elimination programs and propose strategies to overcome this challenge and achieve the goal of elimination. By addressing the diagnostic and therapeutic gaps, optimizing surveillance and control measures, and implementing effective intervention strategies, it is possible to mitigate the burden of PKDL and facilitate the successful elimination of VL in the Indian sub-continent.